Psychological management of vitiligo during the COVID-19 pandemic - Farhat Fatima; Anupam Das; Mohammad Jafferany (Wolters Kluwer Medknow Publications, 2020)
COVID-19 pandemic has changed our outlook toward the diagnosis and treatment of dermatological conditions. Accessibility to health care facilities has been jeopardized due to lockdowns, fear of contracting COVID infection, maintaining social distance, and financial concerns. Vitiligo, one of the notorious chronic dermatoses, had a negative impact on the quality of life of patients, even during pre-COVID era. Now, with the arrival of the pandemic, patients are unable to seek consultation for the disease. Stress being one of the key players in the pathogenesis of the disease, is leading to exacerbation of the condition. In this review, we have attempted to highlight the role of psychological management of vitiligo, amidst the ongoing pandemic